Amyloid Positivity Using [18F]Flutemetamol-PET and Cognitive Deficits in Nondemented Community-Dwelling Older Adults. (September 2017) - Hammers, Dustin B.; Atkinson, Taylor J.; Dalley, Bonnie C. A.; Suhrie, Kayla R.; Horn, Kevin P.; Rasmussen, Kelli M.; Beardmore, Britney E.; Burrell, Lance D.; Duff, Kevin; Hoffman, John M.
Little research exists examining the relationship between beta-amyloid neuritic plaque density via [18F]flutemetamol binding and cognition; consequently, the purpose of the current study was to compare cognitive performances among individuals having either increased amyloid deposition (Flute+) or minimal amyloid deposition (Flute−). Twenty-seven nondemented community-dwelling adults over the age of 65 underwent [18F]flutemetamol amyloid-positron emission tomography imaging, along with cognitive testing using the Repeatable Battery for the Assessment of Neuropsychological Status (RBANS) and select behavioral measures. Analysis of variance was used to identify the differences among the cognitive and behavioral measures between Flute+/Flute− groups. Flute+ participants performed significantly worse than Flute− participants on RBANS indexes of immediate memory, language, delayed memory, and total scale score, but no significant group differences in the endorsed level of depression or subjective report of cognitive difficulties were observed. Although these results are preliminary, [18F]flutemetamol accurately tracks cognition in a nondemented elderly sample, which may allow for better prediction of cognitive decline in late life.